2016
DOI: 10.1093/jat/bkw031
|View full text |Cite
|
Sign up to set email alerts
|

Carboxy-THC in Washed Hair: Still the Reliable Indicator of Marijuana Ingestion

Abstract: The presence of the metabolite 11-nor-9-carboxy-delta-9-tetrahydrocannabinol (C-THC) in hair is generally accepted as the definitive proof of delta-9-tetrahydrocannabinol (THC) ingestion. During hair analysis, the removal of any potential C-THC external contamination that could result from marijuana smoke or close personal contact via a wash procedure is critical. Here, we performed a series of experiments to demonstrate that C-THC is the reliable indicator of marijuana ingestion when paired with the correct w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…15 A series of experiments including heavy smoke exposure; cross contamination in the presence of moisture from THC-COOH-positive hair or fabric, respectively; or soaking of hair in THC-COOH solutions of 10 pg/mL showed that an adequate washing procedure is able to completely remove potential external contamination. 16 Reportedly, the LLOQ of the analytical method applied was 0.1 pg THC-COOH/mg hair being 2 times lower than the LLOQ recom- Although analysis of a higher number of hair samples will be desirable, this study extends the previously published literature. A higher number of samples has been evaluated for cannabis use than previously reported.…”
Section: Comparison Of the Results For Thc Thc-cooh Und Thc-oh Frmentioning
confidence: 62%
See 1 more Smart Citation
“…15 A series of experiments including heavy smoke exposure; cross contamination in the presence of moisture from THC-COOH-positive hair or fabric, respectively; or soaking of hair in THC-COOH solutions of 10 pg/mL showed that an adequate washing procedure is able to completely remove potential external contamination. 16 Reportedly, the LLOQ of the analytical method applied was 0.1 pg THC-COOH/mg hair being 2 times lower than the LLOQ recom- Although analysis of a higher number of hair samples will be desirable, this study extends the previously published literature. A higher number of samples has been evaluated for cannabis use than previously reported.…”
Section: Comparison Of the Results For Thc Thc-cooh Und Thc-oh Frmentioning
confidence: 62%
“…Although having been questioned, detection of THC‐COOH is generally accepted as proof of cannabis use . A series of experiments including heavy smoke exposure; cross contamination in the presence of moisture from THC‐COOH‐positive hair or fabric, respectively; or soaking of hair in THC‐COOH solutions of 10 pg/mL showed that an adequate washing procedure is able to completely remove potential external contamination …”
Section: Resultsmentioning
confidence: 99%
“…It has even been suggested that a major part of THC detectable in a drug smoker's hair actually originates from external contamination . The presumption of Moosmann et al that THC‐COOH could also be present in hair samples of non‐consuming individuals due to contamination by cannabis consumers via sebum/sweat has been challenged in a review by Berthet et al and the investigation of Hill et al…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was also described by other scientific research groups [7,8], and can be explained by the assays' limited sensitivity to detection of cannabis in hair samples. On the opposite side, other scientific researcher's states a scientific evidence of detection of cannabis abuse by means of hair analysis should involve the sensitive detection of the THC metabolite THC carboxylic acid (THC-COOH) in a very lower detection limit, (pg) detection unit [9][10][11].…”
Section: Resultsmentioning
confidence: 99%